Pengetahuan dan Ukuran Kebenaran dalam Kajian Filsafat - Muh. Misbah; Asep Kusnadi (Andragogia: Journal Education Science And Islamic Studies, 2024)
Knowledge is the result of human knowledge to understand an object they encounter, as a result of efforts to understand a particular object. Discussing knowledge is always linked to epistomology, which is a branch of philosophy that discusses the occurrence of knowledge, sources of knowledge, origins of knowledge, boundaries, nature, methods and validity of knowledge. The measure of truth as a process of validity of knowledge. Epistomologically, truth is the correspondence between what is claimed to be known and the actual reality which is the object of knowledge. Truth lies in the correspondence between subject and object, namely what the subject knows and reality as it is. There are four theories of truth; 1) correspondence theory, 2) Coherence theory, 3) pragmatic theory, 4) religious truth.